-3(2x-6)-4x+9=

Simple and best practice solution for -3(2x-6)-4x+9= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2x-6)-4x+9= equation:


Simplifying
-3(2x + -6) + -4x + 9 = 0

Reorder the terms:
-3(-6 + 2x) + -4x + 9 = 0
(-6 * -3 + 2x * -3) + -4x + 9 = 0
(18 + -6x) + -4x + 9 = 0

Reorder the terms:
18 + 9 + -6x + -4x = 0

Combine like terms: 18 + 9 = 27
27 + -6x + -4x = 0

Combine like terms: -6x + -4x = -10x
27 + -10x = 0

Solving
27 + -10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + -10x = 0 + -27

Combine like terms: 27 + -27 = 0
0 + -10x = 0 + -27
-10x = 0 + -27

Combine like terms: 0 + -27 = -27
-10x = -27

Divide each side by '-10'.
x = 2.7

Simplifying
x = 2.7

See similar equations:

| 7y+1=8y+5 | | x^2-x+64=0 | | 6x^2+12x+c=0 | | 8x+17=5x+35 | | x^2+4x+48=0 | | 8/x-5x=4 | | 5x^2-78=48 | | a=10ln(a) | | x-1-(x-2)(x+2)=9 | | 7.5m+1.1-10m=4.3-2.5m-3.2+1.7 | | 2x-8x+29=5 | | -3(-2)+y=-5 | | 6y/z | | -39-20+y=-5 | | -13-4x=-21 | | 2*(x+3)=a | | -20x^2+12x+27=0 | | 2x(x+3)=a | | 0=6x^2+6 | | 5(x-1)-2(x^2+5x+6)-7(x+6)= | | x+3/10=-3/10 | | 6x(x-2)=11 | | -6+4x=34 | | -7b+4=39 | | 7-4m=51 | | 8x-2+3x+4= | | 14-y=18 | | -12+5x=-2 | | 10+7b=52 | | -7+4t=-23 | | 7n-6=-83 | | -4b-2=-2 |

Equations solver categories